PUBLIC PERCEPTION OF THE POTENTIAL OF WATERFALL TOURISM IN BENGKULU PROVINCE AFTER THE ENACTMENT OF THE NEW NORMAL COVID PANDEMIC 19 - Wagini; Suswati Nasution; Tito Irwanto (Universitas Terbuka, 2020)
The purpose of this study was to determine public perceptions about the tourism potential of the Waterfall in Bengkulu Province. By taking six waterfall tourism objects in three regencies namely North Bengkulu Regency, Bengkulu Tengah Regency and Kepahing Regency, each regency has two waterfall ojek tourism objects studied. , where the assessment of perceptions concerns the accessibility to the waterfall, infrastructure supporting the accessibility of the waterfall, security of the location of the waterfall, promotion and marketing, the organization managing the object of the waterfall, the presence or absence of community economic activities, the presence or absence of the tourism industry, and environmental comfort including protocols health deter covid pandemic 19. This type of research is a survey research with quantitative and qualitative analytical descriptive methods, where the questionnaire as the main tool for data collection, data analysis uses an average distribution with measurement of 5-point Likert scale and frequency distribution with the help of SPSS software . The results showed that the public perception of the potential of the waterfalls studied at six locations of waterfalls that were examined were good. Based on the perception of the people studied, most respondents felt that the indicators were good, this certainly could be used as input for the local government in order to further improve the improvement indicators requested by the community. The results of this study can be used as a basis by decision makers in Bengkulu Province because most districts all have waterfall tourist destinations. This tourism potential cannot be ignored, especially in the New Normal Era, tourists prefer to be friends with nature.